(untitled) (Bangladesh Journal of Medical Biochemistry, 2025)
Numerous anthropometric indices can be used to evaluate obesity, which have been linked to type 2 diabetes mellitus (T2DM) and cardiometabolic risk. While the National Institutes of Health (NIH) advocated measuring waist circumference (WC) at the superior border of the iliac crest as the preferable method for central obesity assessment, the World Health Organization (WHO) and International Diabetes Federation (IDF) both recommended WC midway. Consequently, the purpose of this study was to assess the predictive power of WC rib measurements for adult T2DM and cardiometabolic risk. A cross-sectional analytical study was conducted during the period of March 2019 to February 2020 at the Department of Biochemistry, Sir Salimullah Medical College, Dhaka, Bangladesh. On fulfilment of the inclusion and exclusion criteria, 125 subjects were enrolled through purposive sampling, and their anthropometric measurements were obtained. After blood collection at fasting condition, high-density lipoprotein cholesterol, serum insulin, triglycerides, and plasma glucose levels were measured. The findings demonstrated that male study participants had greater mean values for weight, height, WC rib, systolic and diastolic blood pressure than female participants. The study showed that compared to female participants, the male subjects showed an aberrant lipid profile and male subjects had a considerably higher prevalence of T2DM and three or more cardiometabolic risks. Additionally, we also observed significant and positive correlation for TG, SBP, DBP, FPG and HOMA-IR with BMI, WC midway, WC rib, hip circumference and pelvic width in both genders. Odds ratio of having 3 or more cardiometabolic risks showed the odds was highest for WC rib and rib derived indices in both genders. In addition, according to ROC analysis, WC rib (AUC=0.716) and rib-derived indices demonstrated considerably greater AUC to identify three or more cardiometabolic risks in male patients. However, WC rib did not provide a greater AUC than WC midway in the case of females. For T2DM, WC rib demonstrated a considerably greater AUC in both genders (AUC=0.68 in male and 0.71 in female). Bangladesh J Med Biochem 2020; 13(2): 31-39